Changes in faecal haemoglobin values over sequential rounds of faecal immunochemical tests (FIT) in a surveillance population - Amanda J Cross; Kate Wooldrage; Gemma Mortell; Gwen A Murphy (BMJ Open Gastroenterology)
Objective Colorectal cancer (CRC) screening enables resection of polyp precursor lesions, preventing cancer or detecting it earlier. Post-polypectomy, people can remain at increased CRC risk, prompting surveillance colonoscopy. Less invasive faecal immunochemical tests (FIT) could reduce the burden of surveillance colonoscopy. We investigated whether changes in FIT values over multiple rounds were associated with advanced colorectal neoplasia (ACN) detection.Methods A cohort of men and women aged 60–72 years deemed intermediate risk by the 2002 UK adenoma surveillance guidelines and scheduled for three yearly colonoscopies were recruited (January 2012–December 2013) within the English Bowel Cancer Screening Programme and offered a quantitative FIT at 1, 2 and 3 years post-baseline colonoscopy for a prospective analysis within a diagnostic accuracy study. Participants positive (≥40 µg haemoglobin/g faeces) at 1 year or 2 years were offered early colonoscopy and excluded, otherwise, colonoscopy was offered at 3 years. Only those who completed three FIT rounds and attended the 3-year colonoscopy were included. Participants were grouped based on changes between FIT rounds, with changes defined as absolute differences ≥4 µg/g, and positivity at round 3.Results Among 4412 participants, the largest group (n=2773) was the no change category, which had the lowest ACN detection rate (4.7%, 95% CI: 3.9 to 5.5). The serial increase group with a positive round 3 value (n=46) had the highest ACN detection rate (32.6%, 95% CI: 19.5 to 48.0).Conclusion No change in FIT result across multiple rounds was associated with a low ACN detection rate, while a serial increase was associated with higher ACN detection rates. Further research should consider if sequential rounds of FIT could be used for stratifying individual risk.